Rationale and design of the Prevent Anal Cancer Self-Swab Study: a protocol for a randomised clinical trial of home-based self-collection of cells for anal cancer screening. Issue 6 (29th June 2021) - Nyitray, Alan G; Schick, Vanessa; Swartz, Michael D; Giuliano, Anna R; Fernandez, Maria E; Deshmukh, Ashish A; Ridolfi, Timothy J; Ajala, Christopher; Brzezinski, Bridgett; Sandoval, Micaela; Nedjai, Belinda; Smith, Jennifer S; et al.
Abstract : Introduction: Squamous cell carcinoma of the anus is a common cancer among sexual minority men, especially HIV-positive sexual minority men; however, there is no evidenced-based national screening protocol for detection of anal precancers. Our objective is to determine compliance with annual anal canal self-sampling or clinician-sampling for human papillomavirus (HPV) DNA. Methods and analysis: This is a prospective, randomised, two-arm clinical study to evaluate compliance with annual home-based versus clinic-based HPV DNA screening of anal canal exfoliated cells. The setting is primary care community-based clinics. Recruitment is ongoing for 400 HIV-positive and HIV-negative sexual minority men and transgender persons, aged > 25 years, English or Spanish speaking, no current use of anticoagulants other than nonsteroidal anti-inflammatory drugs and no prior diagnosis of anal cancer. Participants are randomised to either receive a swab in the mail for home-based collection of an anal canal specimen at 0 and 12 months (arm 1) or attend a clinic for clinician collection of an anal canal specimen at 0 and 12 months (arm 2). Persons will receive clinic-based Digital Anal Rectal Examinations and high-resolution anoscopy-directed biopsy to assess precancerous lesions, stratified by study arm. Anal exfoliated cells collected in the study are assessed for high-risk HPV persistence and host/viral methylation. The primary analysis will use the intention-to-treat principle to compare the proportion of those who comply with 0-month and 12-month sampling in the home-based and clinic-based arms. The a priori hypothesis is that a majority of persons will comply with annual screening with increased compliance among persons in the home-based arm versus clinic-based arm. Ethics and dissemination: The study has been approved by the Medical College of Wisconsin Human Protections Committee. Results will be disseminated to communities where recruitment occurred and through peer-reviewed literature and conferences. Trial registration number: NCT03489707 .